Outcomes of olecranon fractures in adolescents: comparison of tension band wiring and Herbert screw fixations - Yang, Weiwei; Zhang, Xintao; Sun, Dong; Jin, Shaobin; Chen, Junfei; Li, Yang (Frontiers in Pediatrics, 2024)
Purpose: Olecranon fracture is considered intra-articular when there is obvious displacement or an irregular articular surface. Such fractures should be reduced and fixed via surgery. No clear indications regarding the surgical technique to be adopted exist. Therefore, this study aimed to compare the outcomes of tension band wiring (TBW) and Herbert screw fixations for olecranon fractures.We retrospectively analyzed the clinical data of 29 children with olecranon fractures. They were divided into the tension band wiring and Herbert screw groups. We assessed early epiphyseal closure and maximum length of the ulna using radiography. Patients were clinically evaluated using the average QuickDASH score.Results: Both groups had good radiological outcomes. Herbert screws demonstrated advantages in terms of bleeding, operative time, intraoperative blood loss, surgery duration, and particularly the QuickDASH score (1.57 vs. 4.18, p < 0.05). Complications, including needle loosening and bursitis, occurred in five cases in the TBW group. Six cases had premature physis plate closure, and no difference was observed in limb length at 6 months after surgery.Compared with TBW, Hebert screws demonstrated better clinical outcomes and lesser postoperative complications in the treatment of ulnar olecranon fractures in children. However, long-term follow-up is required to assess the effects of screws on the ulnar physis plate and ulna length.